Identifying EFL Students Learning Styles in the Context of Afghanistan - Sayed Bashir Aalemy; Ahmad Jan Amiry (RIRAI Publisher, 2022)
In recent years, great attention was paid to the factors of individual differences in EFL context, especially the learner learning styles. The main purpose of this study is to determine the learning styles of Parwan university EFL learners. A mixed method of research (quantitative and qualitative) was considered in order to collect and analyze the data. A total of 110 EFL Parwan university students (90 males) and (20 females) were participated in this study. The results of descriptive statistics indicated that the majority of the participant 81 % positively valued the visual learning styles. In addition, the findings showed that 53 % of the participants preferred auditory learning styles while 66 % of them determined as kinesthetic learners.